Nghiên cứu cơ chế sự tạo thành sản phẩm hydro, etylen và etylen oxit trong phản ứng gốc metylidin với metanol - Thọ, Nguyễn Hữu; Huệ, Nguyễn Minh; Quang, Dương Tuấn (Vietnam Journal of Chemistry, 2012)
The reaction mechanism of the methylidene radical (CH) with methanol (CH3OH) has been studied by the Density Functional Theory (DFT) using the BHandHLYP functional in conjunction with the aug-cc-pvdz and aug-cc-pvtz. The potential energy surfaces describing these processes were been constructed. The products of H2+CHCHOH, H2+COCH3, H2+HCOCH2 and CH2OCH2(cycle)+H have been found. The present work indicates that a transition state exists during the process forming C2H4. Our results contribute to a more complete understanding about the reaction mechanism of the CH radical with CH3OH.